Upaya Peningkatan Produktifitas Pengusaha Lele Melalui Mesin Pelet Lele - Akhmad Afandi; Nuraini Lusia; Naris Wari (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Application technology for society of catfish’s entrepreneur has been done in Kedungrejo village, Muncar district. The purpose of this activity to improve the knowledge of partners for catfish’s business, appropriate technology for making pellet has been applicated to decrease the cost of catfish feed (pellet). The target reached is producing appropriate technology for catfish feed mould, improvement knowledge of partner in catfish business was marked with increasing capability to make catfish feed independently and increasing the number of catfish harvested 50-70%.  The result of this activity is the creation of catfish feed with drying system machine. The improvement of knowledge in operating and maintenance of that machine through the training by the dedication team. By the appropriate technology of catfish feed with drying system machine, the income of catfish business was increased 70% from the total cost. This activity was very advantages for the partners